Ghosthunters and the incredibly revolting ghost - Funke, Cornelia 1958-; Ragg-Kirkby, Helena (New York : Scholastic, 2006)
A timid boy named Tom reluctantly agrees to help professional ghostbuster Hetty Hyssop dispel an IRG (Incredibly Revolting Ghost) from an old house.
A horrible day -- Teased and scorned! -- Hetty Hyssop -- Slimy trails in the dark -- A terrible story -- A serious problem -- The book of ghosts -- A wailing and gnashing of teeth -- A bucketful of graveyard dirt -- Nothing but trouble -- The haunted villa -- Chattering teeth and knocking knees -- The plan -- The ghost hunt -- Revenge.
b
b
Keywords: Ghost stories; Ghosts -- Fiction